Plasma Spray Coating of an AA 2024-T4 Al Alloy with Oxide Powders - Ozel, Serkan; Turhan, Huseyin (Carl Hanser Verlag, 2010)
In this study, the surface of AA2024-T4 Al alloy substrate was coated by Al(2)O(3) + TiO(2) powders without and with NiAl bond coat by using a plasma spray process. The TiO2 content was added at different concentrations (3, 13 and 40 wt.-%) to the Al(2)O(3) content. The coated samples were characterized by means of an optical microscope, scanning electron microscope (SEM), energy dispersive X-ray spectroscopy (EDX), and the hardness as well as the bond strength were tested. These results showed that the hardness and porosity decreased with the increasing of the TiO(2) content of the Al(2)O(3) + TiO(2) coatings. The bonding strength of the coated specimens was increased by using the NiAl bond coat.
Keywords: Mechanical-Properties; Microstructure; Behavior; Alumina; Titania; Aa2024; Tio2